Miniaturized pattern formation in elastic films cast on sinusoidally patterned substrates - Annepu, Hemalatha (Langmuir : the ACS journal of surfaces and colloids, 2014)
The various morphologies that are formed when van der Waals forces or electric field is induced between film cast on a sinusoidal substrate and in contact proximity with a contactor or electrode are studied. Remarkably smaller length scales are achieved (λc < 2.96h) than those obtained with films cast on flat substrates. With van der Waals interactions, the patterns are uniformly formed throughout the film but are not regularly ordered. When electric field is used at critical voltage, more ordered, localized patterns are formed at the zones of large local interaction strengths. When these patterns are evolved by increasing the applied voltage, coexistence of all three phases-cavities, stripes, and columns-is observed throughout the film. The localized patterns that are initially formed vary with the voltage applied and strongly dictate the phases of evolution. A patterned substrate/patterned contactor assembly can be made to operate like its unpatterned counterpart by making the interaction strength same everywhere and yet yield uniform, regularly ordered, highly miniaturized patterns. Such patterns are very useful in various applications like microfluidics; they are formed with great ease and can be morphologically tuned by tuning the externally applied electric field